2007
DOI: 10.1152/ajprenal.00148.2006
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of acid, basic, and neutral peptidase activity and expression in human clear cell renal cell carcinoma

Abstract: Peptides play important roles in cell regulation and signaling in many tissues and are regulated by peptidases, most of which are highly expressed in the kidney. Several peptide convertases have a function in different tumor stages, and some have been clearly characterized as diagnostic and prognostic markers for solid tumors, including renal cancer; however, little is known about their in vivo role in kidney tumors. The present study compares the activity of a range of peptidases in human tumor samples and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 39 publications
7
25
1
Order By: Relevance
“…However, the mRNA levels of Asp-AP, APA, APB, and PGI were not in concordance with our data on peptidase activity. We reported a similar pattern of expression in our previous study on CCRCC (37).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the mRNA levels of Asp-AP, APA, APB, and PGI were not in concordance with our data on peptidase activity. We reported a similar pattern of expression in our previous study on CCRCC (37).…”
Section: Discussionsupporting
confidence: 86%
“…Renal parenchyma is a tissue very rich in both soluble and particulate peptidases (24,31). We previously reported significant alterations in the activity and the expression profiles of several of the aforementioned enzymes when human samples of primary CCRCC were compared with their surrounding uninvolved tissue (37). Interestingly, with the exception of puromycin-sensitive aminopeptidase (PSA; EC 3.4.11.14), a soluble activity which increased in CCRCC, all the peptidases showing alterations of activity in tumor cells were downregulated.…”
mentioning
confidence: 99%
“…Note that aminopeptidase B was predicted to be able to bind directly with GAD in the INVDOCK analysis of present study. And it was reported that the aminopeptidase B activity was decreased in human renal cell carcinoma samples compared with non-tumor tissues (49). The increase of aminopeptidase B protein expression in GAD-treated HeLa cells may play an important role in the cytotoxicity of GAD.…”
Section: Figmentioning
confidence: 92%
“…There may be an impression that blood exopeptidases are non-specific enzymes that are not under differential regulation between physiological states (Sanderink, Artur, & Siest, 1988;Diamandis, 2006a). However there are multiple reports of disease specific exopeptidase activity as a markers or mechanisms of disease in blood, tissues and cells (Elgun, Karaayvaz, & Durak, 1997;Simaga et al, 1998;Martinez et al, 1999;van Hensbergen et al, 2002;Davis et al, 2005;Varona et al, 2007). Furthermore a statistical model of peptidome degradation using the Metropolis-Hastings algorithm for Bayesian inference of model parameters and other mathematical models supported the hypotheses of disease-specific exopeptidase activity Kluge, Gambin, & Niemiro, 2009).…”
Section: A Endopeptidase Versus Exopeptidasementioning
confidence: 99%